فاعلية برنامج تعليمي مصمم وفق طريقتي مونتيسوري والتعليم الملطف في تنمية مهارات التحدث لدى التلاميذ من ذوي صعوبات التعلم في مرحلة التعليم الأساسي في الجمهورية اليمنية - السراجي، أمة العزيز عبدالعزيز (مركز فكر للدراسات والتطوير, 2023)
هدف البحث إلى التعرف على فاعلية برنامج تعليمي مصمم وفق طريقتي مونتيسوري والتعليم الملطف في تنمية مهارات التحدث لدى التلاميذ من ذوي صعوبات التعلم في مرحلة التعليم الأساسي في الجمهورية اليمنية، معتمدا على المنهجين (الوصفي وشبه التجريبي)، ولتحقيق هدف الدراسة، تم إعداد اختبار تحصيلي وعرضه على المحكمين في مناهج اللغة العربية وطرائق تدريسها لتحكيم صدقه، وتكونت عينة البحث من (30) تلميذة من الصف الرابع ممن يعانين من صعوبات التعلم وهي عينة قصدية من مدرسة سمية وسكينة للتعليم الأساسي (للبنات) وهما من مدارس الدمج الشاملة التابعة لوزارة التربية والتعليم، وتم تقسيمهم إلى مجموعتين تجريبيتين قوام كل من هما (15) تلميذة، وأظهرت نتائج البحث وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسط رتب درجات مجموعة مونتيسوري والتعليم الملطف في التطبيق البعدي لبطاقة الملاحظة لإجمالي مهارات التحدث لصالح المجموعة التي خضعت لطريقة التعليم الملطف. وفي ضوء النتائج تم اقتراح عدد من التوصيات منها: ضرورة توظيف طريقة مونتيسوري والتعليم الملطف بأسس علمية في تدريس اللغة العربية لتلاميذ المرحلة الأساسية بشكل عام، والتلاميذ ذوي صعوبات التعلم بشكل خاص. The aim of the research is to identify the effectiveness of an educational program designed according to the two methods of Montessori and palliative education in developing the speaking skills of students with learning difficulties in the basic education stage in the Republic of Yemen, based on the two approaches (descriptive and semi-experimental), and to achieve the objective of the study, an achievement test was prepared and presented The arbitrators in the curricula of the Arabic language and the methods of teaching it to judge his sincerity, and the research sample consisted of (30) students from the fourth grade who suffer from learning difficulties. They were divided into two experimental groups consisting of (15) female students each, and the results of the research showed that there were statistically significant differences at the level (0.01) between the mean scores of the Montessori group and soft education in the post application of the note card for the total speaking skills in favor of the group that underwent the method of soft education. . In light of the results, a number of recommendations were proposed, including: the need to employ the Montessori method and palliative education on scientific basis in teaching Arabic to basic stage students in general, and students with learning difficulties in particular.
Keywords: التعلم الملطف -- البرامج التعليمية -- طرق التدريس -- صعوبات التعلم -- اليمن